Evidence for the role of histaminergic pathways in neuroprotective mechanism of ischemic postconditioning in mice. (4th April 2017) - Kaur, Indresh; Kumar, Amit; Jaggi, Amteshwar S.; Singh, Nirmal
Abstract: The present study has been designed to investigate the possible role of histaminergic pathway in neuroprotective mechanism of ischemic postconditioning (iPoCo). Bilateral carotid artery occlusion (BCAO) for 12 min followed by reperfusion for 24 h was employed to produce I/R‐induced cerebral injury in National Institutes of Health mice mice. iPoCo involving three episodes of carotid artery occlusion and reperfusion of 10 sec each was instituted immediately after BCAO just before prolonged reperfusion. Cerebral infarct size was measured using triphenyltetrazolium chloride staining. Memory was evaluated using Morris water maze test. Rotarod test, inclined beam‐walking test, and neurological severity score (NSS) were performed to assess motor incoordination and sensorimotor abilities. Brain acetylcholine esterase (AChE) activity, brain myeloperoxidase (MPO) activity, brain thiobarbituric acid‐reactive species (TBARS), and glutathione level (GSH) were also estimated. BCAO produced a significant rise in cerebral infarct size and NSS along with impairment of memory and motor coordination and biochemical alteration (↑AChE, ↑MPO ↓GSH, and ↑TBARS). iPoCo attenuated the deleterious effect of BCAO on infarct size, memory, NSS, motor coordination, and biochemical markers. Pretreatment of carnosine (a histamine [HA] precursor) potentiated the neuroprotective effects of iPoCo, whereas pretreatment of ketotifen (HA H1 receptor blocker and mast cell stabilizer) abolished the protective effects of iPoCo as well as that of carnosine on iPoCo. It may be concluded that neuroprotective effect of iPoCo probably involves activation of histaminergic pathways.